Alcohol Impairs Immunometabolism and Promotes Naïve T Cell Differentiation to Pro-Inflammatory Th1 CD4+ T Cells - McTernan, Patrick M.; Levitt, Danielle E.; Welsh, David A.; Simon, Liz; Siggins, Robert W.; Molina, Patricia E. (Frontiers in Immunology, 2022)
CD4+ T cell differentiation to pro-inflammatory and immunosuppressive subsets depends on immunometabolism. Pro-inflammatory CD4+ subsets rely on glycolysis, while immunosuppressive Treg cells require functional mitochondria for their differentiation and function. Previous pre-clinical studies have shown that ethanol (EtOH) administration increases pro-inflammatory CD4+ T cell subsets; whether this shift in immunophenotype is linked to alterations in CD4+ T cell metabolism had not been previously examined. The objective of this study was to determine whether ethanol alters CD4+ immunometabolism, and whether this affects CD4+ T cell differentiation. Naïve human CD4+T cells were plated on anti-CD3 coated plates with soluble anti-CD28, and differentiated with IL-12 in the presence of ethanol (0 and 50 mM) for 3 days. Both Tbet-expressing (Th1) and FOXP3-expressing (Treg) CD4+ T cells increased after differentiation. Ethanol dysregulated CD4+ T cell differentiation by increasing Th1 and decreasing Treg CD4+ T cell subsets. Ethanol increased glycolysis and impaired oxidative phosphorylation in differentiated CD4+ T cells. Moreover, the glycolytic inhibitor 2-deoxyglucose (2-DG) prevented the ethanol-mediated increase in Tbet-expressing CD4+ T cells but did not attenuate the decrease in FOXP3 expression in differentiated CD4+ T cells. Ethanol increased Treg mitochondrial volume and altered expression of genes implicated in mitophagy and autophagosome formation (PINK1 and ATG7). These results suggest that ethanol impairs CD4+ T cell immunometabolism and disrupts mitochondrial repair processes as it promotes CD4+ T cell differentiation to a pro-inflammatory phenotype.